Do some IAA proteins have two repression domains? - Li, Hanbing (Landes Bioscience, 2011)
The plant hormone auxin regulates the transcription of specific genes through the interplay of Auxin Response Factors (ARFs) and Aux/IAA (IAA) repressors. We have recently shown that stabilized IAA repressors with identical amino acid substitutions in their conserved repression domains (i.e., domain I) confer either “low auxin” or “high auxin” phenotypes when the IAA proteins are constitutively expressed in transformed Arabidopsis plants. We have suggested that when domain I loses its capacity to repress, “high auxin” phenotypes generally result, but a subset of IAA proteins (e.g., IAA17) appear to contain a second repression domain resulting in the maintenance of “low auxin” phenotypes. Here we provide evidence for a second repression domain that lies between domains I and II in IAA7, an IAA repressor within the same clade as IAA17.